Evaluation and Validation of the Method of Moments Code NEC2 in the Design of Log Periodic Dipole Arrays With Low Sidelobe Levels for Broadcast Applications - Baker, D. C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The evaluation and validation of the Method of Moments Numerical Electromagnetics Code (NEC2) is undertaken by the comparison of measured and computed radiation patterns of Log Periodic Dipole Arrays. Emphasis is placed on the correspondence of the sidelobe levels -30 to -40 dB down from the major lobe. This paper is concerned with the evaluation of a single antenna in free space.